1995
DOI: 10.1007/bf02220466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hiatal hernia on esophageal manometry and pH-metry in gastroesophageal reflux disease

Abstract: An increased frequency of reflux events and a prolonged acid clearance have been shown in gastroesophageal reflux (GER) patients with a hiatal hernia as compared to those without. The objective of the present study was to further investigate esophageal motility and patterns of reflux in GER patients, in relation to the presence or absence of hiatal hernia. Esophageal manometry and ambulatory 24-hr esophageal pH-metry were used in 42 patients with GER and 18 controls. Eighteen of the patients were considered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
3
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 23 publications
0
42
3
3
Order By: Relevance
“…It also contrasts with the results of a study on 95 patients in which subjects with hiatal hernias ≥ 3 cm were found to have a more abnormal refluxate clearance than subjects without a hernia or with a hernia <3 cm [32]. Further, the acid exposure time [33][34][35][36], the incidence of pathological reflux [38], and the frequency or severity of esophagitis [34,35] were observed to be significantly greater in patients with than in those without hiatal hernia. The failure to detect such a relationship in the present study may be due to the fact that only 30 of our 116 patients had hiatal hernias >3 cm in axial length and 41 were devoid of a hernia.…”
Section: Discussioncontrasting
confidence: 82%
“…It also contrasts with the results of a study on 95 patients in which subjects with hiatal hernias ≥ 3 cm were found to have a more abnormal refluxate clearance than subjects without a hernia or with a hernia <3 cm [32]. Further, the acid exposure time [33][34][35][36], the incidence of pathological reflux [38], and the frequency or severity of esophagitis [34,35] were observed to be significantly greater in patients with than in those without hiatal hernia. The failure to detect such a relationship in the present study may be due to the fact that only 30 of our 116 patients had hiatal hernias >3 cm in axial length and 41 were devoid of a hernia.…”
Section: Discussioncontrasting
confidence: 82%
“…When examining GERD in the context of hiatus hernia, certain distinctions become evident. Patients with more severe forms of GERD, such as erosive esophagitis and Barrett's metaplasia, almost invariably have a hiatus hernia (2,18), and GERD patients with hiatus hernia have increased esophageal acid exposure compared with patients without hiatus hernia (8,18). The mechanistic profile for reflux in hiatus hernia patients is also distinct.…”
mentioning
confidence: 99%
“…Sloan and Kahrilas employed concurrent videofluoroscopy and esophageal manometry to assess the impact of hiatal hernias on esophageal emptying, finding impaired esophageal emptying in nonreducing hernias compared to controls due to "late retrograde flow," suggesting impaired EGJ competence [82]. Likewise, the presence of hiatal hernias in GERD is associated with higher extent of reflux and lower amplitude of distal esophageal body peristalsis [83], while large hiatal hernias (> 3 cm) are associated with a shorter and weaker LES compared to small or no hiatal hernias [84].…”
Section: Barium Radiographymentioning
confidence: 96%